Pneumoretinopexy In Unusual Situations : Our Experience - Kalpana Badami Nagaraj; Shilpa Y Devegowda; Kavitha L Tumbadi; Bhavna Govindaraj; Ridhi Bhandary; Spurti Nataraj; Vishrutha Sushekar (Delhi Journal of Ophthalmology)
Aim: To report the anatomical and visual outcome in patients who underwent pneumoretinopexy (PnR) as a primary procedure in unusual situations. Material Method: A prospective interventional analysis of 5 patients who underwent PnR as the primary treatment for rhegmatogenous retinal detachment (RRD), where either scleral buckling / vitrectomy was advised. Of the 5 patients with RRD, 1st had left eye subtotal RRD with superotemporal break of more than 1 clock hour size with grade A PVR changes, 2nd had left eye subtotal RRD with superonasal break with grade A PVR changes with torticollis, 3rd had left eye near total RRD with superotemporal break with grade A PVR changes, 4th was one-eyed with right eye total RRD with superior break with grade C PVR changes, and 5th had right eye temporal RRD with 2 retinal breaks which were more than 2 clock hours apart with grade A PVR changes. Trial of PnR with appropriate head positioning was done in all patients. Patients were followed up on postoperative day 1,1 week, 1 month and 6 months. Anatomical and visual outcomes were assessed. Results: All patients had good anatomical and visual outcomes. Conclusion: PnR can be considered as a primary treatment option in some simple RRDs with early PVR changes, even though they are not the ideal indications. It can also be useful in the management of RRDs, where there is a limitation for scleral buckling / vitrectomy.